1998
DOI: 10.1091/mbc.9.5.1149
|View full text |Cite
|
Sign up to set email alerts
|

Themedial-Golgi Ion Pump Pmr1 Supplies the Yeast Secretory Pathway with Ca2+and Mn2+Required for Glycosylation, Sorting, and Endoplasmic Reticulum-Associated Protein Degradation

Abstract: The yeast Ca2+ adenosine triphosphatase Pmr1, located in medial-Golgi, has been implicated in intracellular transport of Ca2+ and Mn2+ ions. We show here that addition of Mn2+ greatly alleviates defects ofpmr1 mutants in N-linked and O-linked protein glycosylation. In contrast, accurate sorting of carboxypeptidase Y (CpY) to the vacuole requires a sufficient supply of intralumenal Ca2+. Most remarkably, pmr1 mutants are also unable to degrade CpY*, a misfolded soluble endoplasmic reticulum protein, and display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
381
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(409 citation statements)
references
References 71 publications
26
381
0
2
Order By: Relevance
“…Up to this point, Pmr1 was the only SPCA member to be extensively characterized. Inactivation of PMR1 resulted in missorting and misprocessing of proteins along the secretory pathway and to N-and O-linked glycosylation defects (3,25). These observations were consistent with depletion of luminal Golgi stores and could be separately corrected by high levels of extracellular Ca 2ϩ and Mn 2ϩ , respectively (25).…”
Section: Secretory Pathway Ca 2؉ -Atpase Defective In Hailey-hailey Dmentioning
confidence: 62%
See 2 more Smart Citations
“…Up to this point, Pmr1 was the only SPCA member to be extensively characterized. Inactivation of PMR1 resulted in missorting and misprocessing of proteins along the secretory pathway and to N-and O-linked glycosylation defects (3,25). These observations were consistent with depletion of luminal Golgi stores and could be separately corrected by high levels of extracellular Ca 2ϩ and Mn 2ϩ , respectively (25).…”
Section: Secretory Pathway Ca 2؉ -Atpase Defective In Hailey-hailey Dmentioning
confidence: 62%
“…Inactivation of PMR1 resulted in missorting and misprocessing of proteins along the secretory pathway and to N-and O-linked glycosylation defects (3,25). These observations were consistent with depletion of luminal Golgi stores and could be separately corrected by high levels of extracellular Ca 2ϩ and Mn 2ϩ , respectively (25). In addition, pmr1 mutants have elevated resting levels of Ca 2ϩ in the cytosol and cannot effectively maintain cellular Ca 2ϩ and Mn 2ϩ homeostasis (33,35,62).…”
Section: Secretory Pathway Ca 2؉ -Atpase Defective In Hailey-hailey Dmentioning
confidence: 72%
See 1 more Smart Citation
“…Organelle-specific Ca 21 ATPases have also been reported for plants [3,33±35]. It has recently been reported that several processes in the Golgi lumen are Ca 21 dependent in mammalian and yeast cells [36,37,39,40]. Therefore, these two active Ca 21 transporters may keep the Ca 21 concentration in the Golgi lumen at high levels.…”
Section: Discussionmentioning
confidence: 98%
“…The endoplasmic reticulum, Golgi, and small vesicles detoxify metals by removing them from the cytoplasm (Durr et al, 1998;Wu et al, 2002). For example, the Eca1 protein located in the endoplasmic reticulum leads to the uptake of manganese and confers manganese tolerance to the cells (Wu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%